2004
DOI: 10.1152/ajpheart.00297.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological plasma ET-1 levels antagonize β-adrenergic dilation of coronary resistance vessels in conscious dogs

Abstract: Lavallée. Pathophysiological plasma ET-1 levels antagonize ␤-adrenergic dilation of coronary resistance vessels in conscious dogs. Am J Physiol Heart Circ Physiol 287: H1476 -H1483, 2004. First published June 17, 2004 10.1152/ajpheart.00297.2004.-On the basis of in vitro experiments showing that endothelin (ET)-1 interferes with smooth muscle ATP-sensitive K ϩ (KATP) channel opening, which is pivotal in ␤-adrenergic coronary dilation, we hypothesized that pathophysiological plasma ET-1 levels impair ␤-adrener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In myocardial cells, endothelin-1 may antagonize b-adrenergic receptors, [17][18][19] but in vascular smooth muscle, the results are conflicting. [20][21][22] We hypothesize that endothelin-1 may modulate the b-adrenergic response of coronary arteries, as it has been described for the a-adrenergic vasoconstriction, thus participating in the regulation of coronary blood flow. Stimulation of b-adrenoceptors in the heart in vivo increases myocardial metabolism and oxygen consumption.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In myocardial cells, endothelin-1 may antagonize b-adrenergic receptors, [17][18][19] but in vascular smooth muscle, the results are conflicting. [20][21][22] We hypothesize that endothelin-1 may modulate the b-adrenergic response of coronary arteries, as it has been described for the a-adrenergic vasoconstriction, thus participating in the regulation of coronary blood flow. Stimulation of b-adrenoceptors in the heart in vivo increases myocardial metabolism and oxygen consumption.…”
Section: Introductionmentioning
confidence: 75%
“…22 On the contrary, in the coronary circulation of dogs, endothelin-1 reduced the b-adrenergic vasodilatation through activation of ET A receptors and inhibition of adenosine triphosphate-dependent potassium channels. 21 This discrepancy may be due to differences in species (dog vs. rat) or in the experimental preparation (in vivo coronary blood flow measurement vs. isolated vascular segments). The potentiating effect of endothelin-1 in rat coronary arteries may be mediated by PKC, as it has been found in rat aorta, 22 because it was abolished by the blocker of this kinase chelerythrine.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Endothelin-1 is a potent vasoconstrictor 2 and regulates arterial tone at rest. 4,5 However, during exercise, endothelin-1 levels decrease facilitating coronary vasodilatation. Work in animals has suggested that high circulating endothelin-1 reduces adenosine-induced coronary vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…NO strongly inhibits the release of ET-1 from the native endothelium [16,17], which makes ET-1 and NO functionally closely interdependent, with a strong inhibitory effect of ET-1 on NO-mediated dilation, including in human coronary and cerebral arteries, and vice versa [14,[18][19][20][21]. The inhibitory effects of ET-1 are not limited to the dilations induced by NO since ET-1, through activation of the protein kinase C pathway, also reduces β-adrenergic receptor-dependent relaxation both in vitro and in vivo [22,23]. This peptide is therefore a potent "anti-vasodilatory" factor released by the endothelium.…”
Section: Physiological Effects Of Et-1 In Arteriesmentioning
confidence: 99%